Coretax Use, E-Billing Use, and Taxpayer Understanding on Annual Tax Reporting Compliance - Yenni Vera Fibriyanti; Indah Kurniyawati; Kholifatun Munawaroh (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the influence of coretax use, e-Billing utilization, and taxpayer understanding on compliance with Annual Tax Return (SPT) reporting among individual taxpayers in Lamongan Regency. This study used a quantitative method with random sampling of individual taxpayers at the Lamongan Pratama Tax Office (KPP Pratama). Data were collected through questionnaires and analyzed using multiple linear regression. The results show that coretax use , e-Billing utilization, and taxpayer understanding have a significant positive effect on compliance with SPT reporting, both partially and simultaneously.